2020
DOI: 10.1016/j.ymgmr.2020.100622
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of N-carbamylglutamate in CPS1 deficiency

Abstract: The detoxification of ammonia to urea requires a functional hepatic urea cycle, which consists of six enzymes and two mitochondrial membrane transporters. The initial step of the urea cycle is catalyzed by carbamyl phosphate synthetase 1 (CPS1). CPS1 deficiency (CPS1D) is a rare autosomal recessive disorder. N -Carbamylglutamate (NCG), a deacylase-resistant analogue of N -acetylglutamate, can activate CPS1. We describe the therapeutic course of a patient suffering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…According to previous studies, a few cases of CPS1 deficiency with only a single-allele mutation have been reported ( Table 2 ) ( 13 - 17 ). Further studies are needed to determine whether or not this patient has mutations in the other alleles that could not be detected through conventional genetic analyses or whether the slightly low CPS1 activity in this patient was further reduced by some acquired factors.…”
Section: Discussionmentioning
confidence: 97%
“…According to previous studies, a few cases of CPS1 deficiency with only a single-allele mutation have been reported ( Table 2 ) ( 13 - 17 ). Further studies are needed to determine whether or not this patient has mutations in the other alleles that could not be detected through conventional genetic analyses or whether the slightly low CPS1 activity in this patient was further reduced by some acquired factors.…”
Section: Discussionmentioning
confidence: 97%
“…CPS1 gene variants may decrease the stability of the CPS1 protein or lower the affinity of the enzyme for NAG [ 18 ]. Therefore, NCG supplementation may improve CPS1 function in some patients through saturation of NAG sites in partial CPS1 deficiency, maximizing CPS1 activation and protecting CPS1 from thermal and proteolytic inactivation [ 2 , 19 ]. However, in other CPS1 variants, NCG may compete with NAG binding instead and decrease residual ureagenesis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a response to carbamylglutamate aids in the diagnosis, it is not in itself diagnostic of NAGS deficiency, as carbamylglutamate has been shown to be effective in some cases of other inherited metabolic disorders by augmenting ureagenesis and decreasing plasma ammonia, including CPS1 deficiency, ornithine transcarbamylase (OTC) deficiency, citrullinemia type I (argininosuccinic acid synthetase deficiency), methylmalonic acidemia (MMA), propionic acidemia (PA), isovaleric acidemia (IVA), carbonic anhydrase VA (CAVA) deficiency, and multiple acyl-CoA dehydrogenase deficiency (MADD). Carbamylglutamate has been used in acute treatment of hyperammonemia in some cases of CPS1 deficiency [47][48][49], OTC deficiency [50], PA [51][52][53][54][55], MMA [51][52][53][54][55][56], IVA [57], CAVA deficiency [58,59], and MADD [60] as well as long-term management of some cases of CPS1 deficiency [48,61], citrullinemia type I [62], OTC deficiency [50], PA [63,64], MMA [64], and MADD [60].…”
Section: Discussionmentioning
confidence: 99%